The Dynamics of Gane Language Shift in the Digital Era: A Paradox of Rejection in Practice and Acceptance in Identity among Senior High School Students - Syahrir Ibnu; Nurhadi Hamka (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The Gane language, an indigenous language in South Halmahera, is at a critical stage of language shift, particularly among the younger generation. This study aims to document the patterns of Gane language use, identify the driving factors of its shift, and analyze the attitudes of senior high school students amidst this phenomenon. Employing a descriptive qualitative approach, data were collected through in-depth interviews with senior high school students, teachers, principals, and community leaders, as well as observations in school and social settings. The findings indicate that the use of the Gane language among students is significantly low, having lost its primary communicative domains to the dominance of Indonesian and Ternate Malay. The primary driving factors are the penetration of technology and social media, peer pressure that associates dominant languages with modernity, and the lack of economic value and prestige of the Gane language. Amidst this situation, a crucial paradox was discovered: students reject the use of the Gane language in practice, yet consciously express positive attitudes, admiration, and a strong desire to preserve it as a symbol of identity. This finding implies that revitalization strategies must be youth-centric, integrating formal school policies (curriculum) with informal, digital community-based movements that are relevant to their world.